2016
DOI: 10.1109/tro.2016.2540623
|View full text |Cite
|
Sign up to set email alerts
|

Learning Physical Collaborative Robot Behaviors From Human Demonstrations

Abstract: Abstract-Robots are becoming safe and smart enough to work alongside people not only on manufacturing production lines, but also in spaces such as houses, museums or hospitals. This can be significantly exploited in situations where a human needs the help of another person to perform a task, because a robot may take the role of the helper. In this sense, a human and the robotic assistant may cooperatively carry out a variety of tasks, therefore requiring the robot to communicate with the person, understand his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
148
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 258 publications
(150 citation statements)
references
References 47 publications
1
148
0
1
Order By: Relevance
“…Certainly, an interesting extension of the motion controller would be the inclusion of automatic generation of an impedance control scheme starting from the automatically generated robot description from [7], [8], which could potentially be combined with the demonstration-driven encoding of the impedance target parameters as in [17], [18]. In addition, approaches to optimize the redundancy resolution, instead of simply adding damping for the null-space motions, could be also considered.…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, an interesting extension of the motion controller would be the inclusion of automatic generation of an impedance control scheme starting from the automatically generated robot description from [7], [8], which could potentially be combined with the demonstration-driven encoding of the impedance target parameters as in [17], [18]. In addition, approaches to optimize the redundancy resolution, instead of simply adding damping for the null-space motions, could be also considered.…”
Section: Discussionmentioning
confidence: 99%
“…The learned distribution of demonstrations can then be used for designing control schemes. For instance, in [12] the robot learns collaborative skills and adapts its impedance behavior from demonstrations. However, to the best of our knowledge, no prior work has been proposed for leveraging the distribution of the demonstrated trajectories for controlling the balance between the controllers autonomy and the human inputs.…”
Section: Related Workmentioning
confidence: 99%
“…In LfD methods, the distribution of the demonstrated trajectories is often modeled, and the learned distribution is leveraged for generalizing the demonstrated behaviors [10], [11]. Recent work on LfD showed that the variance of the demonstrated trajectories can be used to adaptively control the robot behaviors [12]. Leveraging the distribution of the demonstrated trajectories into the design of shared control frameworks seems, therefore, a meaningful/promising approach for obtaining a shared control framework able to adjust online the balance between the robot autonomy and the human preference.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, our work can be compared to (Amor et al, 2014;Medina et al, 2012;Rozo et al, 2016;Wrede et al, 2013) where the user and the robot have to execute a learned task together. Regarding the definition of the virtual guides through PbD, our work can be compared to the work done by (Vakanski et al, 2012;Mollard et al, 2015;Boy et al, 2007;Ewerton et al, 2016;Lee and Ott, 2011;Sanchez Restrepo et al, 2017) where the concept of Task refinement is exploited, as we will see in Section 6 this is possible due to the incremental training of GMM .…”
Section: Related Workmentioning
confidence: 99%